'Traditional values' and the narrative of gay rights as modernity: Sexual politics beyond polarization. (January 2023) - Edenborg, Emil
Examining the Russian state's turn to 'traditional values' in the 2010s, this article aims to understand traditionalist state discourses in a global context where LGBT inclusion has been incorporated into notions of national exceptionalism. It argues that the Putin regime has articulated, provided ideological coherence to, and made visible a narrative according to which resistance to LGBT rights appears as a logical choice for states seeking to position themselves in opposition to the 'liberal West.' That narrative both counters the homonationalist idea of 'gay-friendliness' as a signifier of modernity and good statehood and incorporates some of its elements, notably externalization of homophobia onto racialized, Muslim Others.